Empowerment of Farmers in Rejang Lebong Regency, Bengkulu Province - Nugraha, Daruna Eka (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2024)
Empowerment is essential for the community to analyze the conditions, potentials, and life problems they face. In this paper, the author examines the core of the study on farmer empowerment in Rejang Lebong Regency, aiming to develop, improve, and optimize farmers in managing the production of their agricultural products. The author employs a qualitative descriptive method to describe aspects related to the observed and studied focus. The data collection method used is document study. The research results conclude that empowerment activities in Rejang Lebong Regency need to be enhanced to meet the target goals. The quality of human resources is inadequate, and community participation is still minimal regarding socialization, education, and capacity training from the local government. The author suggests that the empowerment process programmed by the government should be carried out according to the target and, if possible, exceed the target. This would ensure that the empowerment goals are felt by the farming community in Rejang Lebong Regency, ultimately moving towards an independent community.